2022
DOI: 10.1016/j.psj.2021.101558
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal mRNA and miRNA transcriptome analyses reveal important genes and miRNAs related to sperm motility in roosters

Abstract: Sperm motility is a crucial trait in chicken production, and the epididymis is an essential organ in the reproductive system. Currently, the molecular mechanisms underlying sperm motility in the epididymis are unclear. In this study, 8 cDNA libraries and eight miRNA libraries were constructed from roosters (4 chickens per group) with diverse sperm motility. After a comparative analysis of epididymal transcriptomes, we detected 84 differentially expressed genes ( DEG s) using the edgeR pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…More recently, extracellular vesicles were found in chicken seminal plasma with different size and proteins markers between fertile and sub fertile males (Cordeiro et al, 2021). Another promising topic is the differences in miRNAs in high-and low-quality semen samples, miRNA patterns can be different depending on the male status and environmental changes, and differences between high and low motility samples were recently described in roosters (Xing et al, 2022). Further work comparing the composition of seminal plasma and the presence of different patterns of miRNAs of ejaculates between different storage time and between old and young males in the houbara bustard would be of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, extracellular vesicles were found in chicken seminal plasma with different size and proteins markers between fertile and sub fertile males (Cordeiro et al, 2021). Another promising topic is the differences in miRNAs in high-and low-quality semen samples, miRNA patterns can be different depending on the male status and environmental changes, and differences between high and low motility samples were recently described in roosters (Xing et al, 2022). Further work comparing the composition of seminal plasma and the presence of different patterns of miRNAs of ejaculates between different storage time and between old and young males in the houbara bustard would be of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that sperm motility in the drakes of HVS group was higher than in the LVS group of the present study also confirmed this point. The important role of sperm motility in the reproduction of poultry has been repeatedly recognized [ 34 , 35 , 36 ]. These results suggested that epididymis could affect the reproductive performance of drakes by regulating semen volume.…”
Section: Discussionmentioning
confidence: 99%
“…The transportation of sperm through vas deferens and sperm storage within the female reproductive tract is important for gaining and maintaining fertility ( Orr and Zuk, 2012 ; Xing et al, 2022 ). Extracellular vesicles transport miRNAs in both paracrine (between cells of the same origin) and endocrine (to distant targets cells) ways ( Yu et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%